2011
DOI: 10.1037/h0100926
|View full text |Cite
|
Sign up to set email alerts
|

Mode deactivation therapy (MDT) comprehensive meta-analysis.

Abstract: Virgin Islands MDT provides an empirically based treatment for adolescents with behavioral problems such as anger, oppositional defiant and sexual and physical aggression (Apsche & DiMeo, 2010). It offers therapists a more efficient and timely intervention that positively effects recidivism rates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 3 publications
0
36
0
1
Order By: Relevance
“…Having met Kazdin's (2007) criteria, this study suggests that MDT has an effect on the reductions of anger and aggression in adolescent males between the ages 14-18, where there also seems to be a relationship between the skillful application of the VCR-FAB and specific variables of anger and aggression. Apsche et al (2011) have demonstrated the overall effectiveness of MDT as compared to CBT in reducing a variety of variables of both externalizing and internalizing disorders. This research focuses on why some of the mediators of change that take place in MDT as a contextual behavioral treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Having met Kazdin's (2007) criteria, this study suggests that MDT has an effect on the reductions of anger and aggression in adolescent males between the ages 14-18, where there also seems to be a relationship between the skillful application of the VCR-FAB and specific variables of anger and aggression. Apsche et al (2011) have demonstrated the overall effectiveness of MDT as compared to CBT in reducing a variety of variables of both externalizing and internalizing disorders. This research focuses on why some of the mediators of change that take place in MDT as a contextual behavioral treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Having met Kazdin's (2007) criteria, this study suggests that MDT has an effect on the reductions of anger and aggression in adolescent males between the ages 14-18, where there also seems to be a relationship between the skillful application of the VCR-FAB and specific variables of anger and aggression. Apsche, Bass, and DiMeo (2011) have demonstrated the overall effectiveness of MDT as compared to CBT in reducing a variety of variables of both externalizing and internalizing disorders. This research focuses on why some of the mediators of change that take place in MDT as a contextual behavioral treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Por eso, consideramos necesario divulgar y alentar la investigación sobre otros modelos de intervención que pudieran aplicase flexiblemente y complementarse para brindar un servicio apropiado para estas personas. En particular, creemos que otros modelos de tc-c pueden auxiliar en esta tarea, pues se combinan fácilmente con estrategias de tdc (Apsche, Bass & DiMeo, 2010;Apsche & DiMeo, 2012;Waltz, Landes & Holman, 2010), potencian sus efectos entre sí y han demostrado eficacia como elementos únicos de tratamiento.…”
Section: Efectividad De Las Tc-cs Para El Tratamiento Del Tlpunclassified